BAP regulates lateral bud outgrowth to promote tillering in Paphiopedilum callosum (Orchidaceae) - Yuying Yin; Ronghui Zhong; Yefei Li; Beiyi Guo; Lin Li; Guohua Ma; Kunlin Wu; Lin Fang; Songjun Zeng (BMC Plant Biology, 2025)
Abstract Background Paphiopedilum orchids have a high ornamental value, and flower abundance is a key horticultural trait. Most Paphiopedilum plants exhibit weak tillering ability, with their tiller buds often entering a dormant state post-formation. Tiller production plays a crucial role in enhancing flower abundance and is potentially regulated by plant hormones. However, the effect of hormones on tillering in Paphiopedilum plants is still unclear. Results In this study, we investigated the promotion of tillering in P. callosum through exogenous root irrigation of benzylaminopurine (BAP). We observed a dose-dependent promotion of tiller production by BAP, with the strongest effect observed at a concentration of 400 mg/L. By comparing the expression of key genes in P. ‘SCBG Yingchun’ (with strong tiller ability) and P callosum (with weak tiller ability), we found that BAP promotes tillering by interacting with abscisic acid (ABA). This interaction involves down-regulation of the ABA degradation gene PcCYP707A, leading to a reduction in ABA content, and the subsequent down-regulation of dormancy-associated genes (PcDRMH1, PcSVP) to release bud dormancy. Additionally, BAP promotes sustained outgrowth of tiller buds by increasing the level of indole-3-acetic acid (IAA) through up-regulation of the IAA synthesis gene PcYUC2 and the transport gene PcPINIC. Conclusions Our results indicated that the application of BAP promotes lateral bud outgrowth and increases tiller production in P. callosum. Through transcriptome analysis, we found that the BAP-promotion of tillering involves not only changes in endogenous IAA, ABA, and CTKs content but is also associated with the regulation of metabolism-related genes and dormancy-associated genes. This study presents the first comprehensive report of BAP-promoted tillering in P. callosum, providing a foundational basis for further mechanistic studies on tiller development in Paphiopedilum species and other non-model plants.